APPLICATION OF META ANALYSIS APPROACH TOWARDS DETERMINING TALENT SHORTAGE IN ISLAMIC BANKING INSTITUTION - Siti Norjannah Jamil; Mohd Ikhwan Aziz; Azwan Abdullah (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
The Islamic banking industry’s rapid global growth, driven by the increasing demand for Sharia-compliant financial solutions, has exposed a significant challenge: talent shortage. Recruiting and retaining skilled professionals in this specialized sector have proven to be formidable obstacles. This meta-analysis systematically reviews existing research articles and reports to uncover the core factors contributing to talent shortages within Islamic banking and propose strategic solutions. The study encompasses various dimensions of talent shortage, including recruitment, retention, skill development, and industry competitiveness. Key factors identified include a lack of awareness and education, cultural and religious barriers, compensation discrepancies, regulatory complexities, and regional disparities in talent availability. The paper offers a multifaceted approach to address these challenges, providing industry stakeholders with a roadmap to cultivate a skilled workforce and align with Islamic principles, thus ensuring long-term growth and prominence in the global financial landscape.